Scanning for New Evidence on Riboflavin to Support a Dietary Reference Intake Review - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Dietary Reference Intakes (DRIs) are a set of evidence-based nutrient reference values for intakes that include the full range of age, gender, and life stage groups in the US and Canada. At the request of the U.S. Department of Agriculture, Agricultural Research Service and the U.S. Department of Health and Human Services, Food and Drug Administration, Center for Food Safety and Applied Nutrition, the National Academies of Science, Engineering, and Medicine convened an ad hoc committee to carry out a literature search and evidence scan of the peer-reviewed published literature on indicators of nutritional requirements, toxicity, and chronic disease risk reduction for riboflavin. Scanning for New Evidence on Riboflavin to Support a Dietary Reference Intake Review builds on the methodology for evidence scanning nutrients (which have existing DRIs) to determine whether there is new and relevant knowledge available that may merit a formal reexamination of DRIs for riboflavin. This report offers comments on the methodological approach to the evidence scan and discusses its findings and interpretation of the process to provide the study sponsors with a greater context to support their interpretation and application of the reported results.
Keywords: Food and Nutrition

Challenges and Opportunities for Precision and Personalized Nutrition: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Food Forum of the National Academies of Sciences, Engineering, and Medicine convened a public workshop exploring potential challenges and opportunities in applying precision and personalized nutrition approaches to optimize dietary guidance and improve nutritional status. The workshop, held on August 10-12, 2021, discussed ways to define both approaches, described current research designs and methodologies in diverse populations, and examined limitations in design and data. The workshop also reviewed innovative methodologies and technologies at the various scales of precision nutrition (including the genetic, physiologic/microbiome, individual, and social-ecologic scales) and discussed challenges and opportunities for implementing these approaches equitably. This Proceedings of a Workshop-in Brief highlights the expert perspectives from academia, the federal government, and industry presented in the workshop.
Keywords: Food and Nutrition